Long-acting antiretrovirals and HIV treatment adherence. Issue 5 (May 2023) - Nachega, Jean B; Scarsi, Kimberly K; Gandhi, Monica; Scott, Rachel K; Mofenson, Lynne M; Archary, Moherndran; Nachman, Sharon; Decloedt, Eric; Geng, Elvin H; Wilson, Lindsay; Rawat, Angeli; Mellors, John W
Summary: Intramuscular injection of long-acting cabotegravir and rilpivirine is a novel, long-acting antiretroviral therapy (ART) combination approved for use as a fully suppressive regimen for people living with HIV. Long-acting cabotegravir with rilpivirine ART has reduced required dosing frequency from once daily to once every month or every 2 months injections. This new era of long-acting ART, which includes other antiretrovirals and formulations in various stages of clinical development, holds tremendous promise to change the standard of HIV treatment. Although long-acting ART has high potential to be revolutionary in the landscape of HIV care, prevention, and treatment cascade, more data are needed to substantiate its efficacy and cost-effectiveness among patients at risk of non-adherence and across age groups, pregnancy, and post partum. Advocacy efforts and policy changes to optimise a sustained, high-quality, equitable reach of long-acting ART, especially in low-income and middle-income countries where most people living with HIV reside, are needed to realise the full benefits of long-acting ART.